Comparative analysis of the repertoire of insulin-reactive B cells in type 1 diabetes-prone and resistant mice - Banach, Maureen; Harley, Isaac T. W.; Getahun, Andrew; Cambier, John C. (Frontiers in Immunology, 2022)
Seropositivity for autoantibodies against multiple islet antigens is associated with development of autoimmune type 1 diabetes (T1D), suggesting a role for B cells in disease. The importance of B cells in T1D is indicated by the effectiveness of B cell-therapies in mouse models and patients. B cells contribute to T1D by presenting islet antigens, including insulin, to diabetogenic T cells that kill pancreatic beta cells. The role of B cell receptor (BCR) affinity in T1D development is unclear. Here, we employed single cell RNA sequencing to define the relationship between BCR affinity for insulin and B cell phenotype during disease development. We utilized immunoglobulin (Ig) heavy chain (VH125) mouse models in which IBCs were previously shown to be anergic in diabetes-resistant VH125.C57BL/6-H2g7 and activated in VH125.NOD mice developing disease. High-affinity insulin-reactive B cells (IBCs) were found in the spleen of prediabetic VH125.NOD mice and exhibited marginal zone or follicular phenotypes. Ig light chains expressed by these B cells are unmutated and biased toward Vκ4-74 and Vκ4-57 usage. Receptors expressed by anergic high-affinity IBCs of diabetes-resistant VH125.C57BL/6-H2g7 are also unmutated; however, these in this genetic background light chains are polymorphic relative to those in of NOD. Light chains derived from NOD and C57BL/6-H2g7 genetic backgrounds conferred divergent kinetics of binding to insulin when paired with the VH125 heavy chain. These findings suggest that relaxation of tolerance mechanisms in the NOD mouse leads to accumulation and partial activation of B cells expressing germline encoded high-affinity BCRs that support development of autoimmunity.